Autologous Advanced Tenon Grafting Combined with Conjunctival Flap in Scleromalacia after Pterygium Excision. (23rd April 2015) - Lee, Jong Soo; Shin, Min Kyu; Park, Jong Ho; Park, Young Min; Song, Margaret
Abstract : Purpose . To evaluate the efficacy of autologous tenon grafting combined with conjunctival flap as a treatment for scleromalacia or scleral thinning after pterygium excision without any additional donor graft tissue. Methods . Twenty-six cases underwent autologous advanced tenon grafting combined with sliding or rotating conjunctival flap for scleromalacia after pterygium surgery ranging from 2 years to 30 years. The extent of scleral defect measured from 2.0 mm to 6.8 mm in diameter. The cosmetic outcome was defined as complete resolution of scleromalacia or completely conjunctival reepithelialization and firm adhesion between subtenon and scleral tissue over scleral thinning without significant complications. Results . All cases achieved the covering of conjunctival and tenon or subtenon tissue over scleromalacia or scleral thinning with this procedure. Preoperative pain, inflammation, and choroidal exposure disappeared after surgery. Immediate postoperative complications, such as large wound dehiscence or reopening of the scleral wound, did not occur in any of the patients. There were no significant clinical complications during the mean postoperative follow-up period of 14.17 months in all cases. Conclusions . We obtained excellent outcome with fewer complications after autologous advanced tenon graft and conjunctival flap, without an additional donor graft, in scleromalacia or scleral thinning caused by previous pterygium excision.